DISPENSER OF THE MERCY OF THE GOVERNMENT: Pardons, Justice, and Felony Disenfranchisement - Rothchild, Jonathan (Journal of religious ethics, 2011)
I argue that the aporetic character of clemency must be understood in terms of its unmerited and merited character to achieve the underlying purposes of justice within criminal justice: justice as fairness (punishment must be deserved and proportionate) and justice as restoration (repair of the harm to victims and society and the reintegration of offenders) are paramount goals. Rather than destabilizing political order, pardons can render productive potential tensions between justice as fairness and justice as restoration. Taking as my conceptual point of departure Paul Ricoeur's claims about the suprajuridical and supraethical character of pardon, I develop the argument through three central sections: an excursus into historical and contemporary practices of clemency in the United States; a critical analysis of the merited and unmerited aspects of clemency with respect to remorse and atonement theories within theological and legal discourse; and a normative engagement with pardons and felony disenfranchisement.